Dari For Your Page ke Formasi Akhlak: Dinamika Algoritma TikTok dalam Membentuk Self-regulated religious behavior Siswa MTs Miftahul Huda Pulosari Kediri - Nanda Ayu Pransischa; Sandi Ferdy Yulianto; Sufirmansyah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
This article aims to analyze the dynamics of the TikTok algorithm in shaping self-regulated religious behavior among students at MTs Miftahul Huda Pulosari Kediri. The focus of the research is directed toward the influence of religious content in the For Your Page (FYP) on the construction of religious meaning, self-regulation, and students' religious behavior. This article uses a qualitative approach with a case study design based on social constructivism. Data were collected thru semi-structured interviews, participatory observations, and documentation of students and teachers who were purposively selected based on the intensity of TikTok usage and exposure to religious content. Data analysis was conducted thru data condensation, data presentation, and conclusion drawing, while data validity was maintained thru triangulation, member checking, and audit trail. The research results show that the TikTok algorithm shapes students' religious experiences thru exposure to personal, repetitive, and engagement-based content. Religious content in the FYP tends to produce affective, fragmentary, and performative religiosity, thereby creating a tension between digital religious visibility and the internalization of religious values in daily life. This article also finds that students' self-regulation of religiosity is influenced by algorithmic exposure and social mediation of madrasahs. Theoretically, this article contributes to the development of digital religiosity studies thru the Algorithmic–Social–Cognitive Religious Formation (ASCRF) model, which explains the interaction between algorithmic systems, cognitive regulation, and social mediation in the formation of students' digital religiosity.